2‐Hydroxy‐4‐methylthio butanoic acid and DL‐methionine for Japanese quails in production. Issue 2 (26th October 2017) - Vieira, D. V. G.; Costa, F. G. P.; Lima, M. R.; Júnior, J. G. de V.; Bonaparte, T. P.; Cavalcante, D. T.
Summary: An experiment was performed using 1, 000 laying Japanese quails to assess the availability of two alternative dietary methionine sources. Treatment 01 = Basal Feed that is deficient in digestible methionine + cystine (Met + Cys). The other treatments were constituted by Met + Cys levels of 0.8, 1.60 and 2.40 g/kg, supplemented with DL‐Methionine‐99%, HMTBA‐88% and HMTBA‐84%, being 10 treatments in total. The following characteristics were studied: feed intake (g/bird/day), egg production (egg/day × 100), egg weight (g/egg), egg mass (g/egg), feed conversion per egg dozen (kg feed/dozen eggs), feed conversion per egg mass (kg feed/kg eggs), relative yolk weight (g/100 g of egg), relative albumen weight (g/100 g of egg), relative shell weight (g/100 g of egg), shell thickness (mm) and specific gravity (g/cm 3 ). In general result comment, supplemental methionine sources must be included in the poultry diet. The different methionine sources affect the performance of quails, and the increase in the levels within each source improves the performance variables. Significant effect was observable on performance variables and egg quality variables, being that DLM‐99% is superior to the other sources. The HMTBA‐88% source is superior to the HMTBA‐84% source for the same aforementioned variables. In conclusion, the bioefficacy values of the HMTBA‐88% and HMTBA‐84% sources compared to the DLM‐99% source on an equimolar basis were 81 and 79%, respectively, for the performance variables, and 83 and 74 while the methionine sources were equivalent for the variables related to egg quality.